Purchasing Criteria for Apparels among Indian Consumers - Kumar, Pawan; Kanchan (Indian Journal of Marketing, 2019)
The present study attempted to evaluate the nature of the fashion industry, and preferential factors accounting for purchasing particular apparels by the customers. The present study was based on primary data and was conducted in four major cities of Punjab, that is, Ludhiana, Sangrur, Patiala, and Chandigarh. By using suitable sampling technique, a sample of 400 respondents was selected for the study. The consumer preferences were assessed on the basis of various parameters like design, quality, price, availability, style, brand image, etc. of the apparels. The study concluded that ’style’ and ’design’ were the first and second preferences of the Indian customers rather than the ’brand name.’ Thus, the apparels organizations are directed to account for these parameters in production and marketing promotional strategies and plans.